2008
DOI: 10.1148/radiol.2483071772
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Abdominal Radiography in the Evaluation of the Nontrauma Emergency Patient

Abstract: Abdominal radiography is often requested; however, its results contribute to patient treatment in a small percentage of cases. With the exception of catheter placement, if a patient requires investigation beyond clinical history, physical examination, and lab results, the emergency physician should be encouraged to request more definitive imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 11 publications
1
57
0
2
Order By: Relevance
“…Most of the patients (33/140) were in age group of [11][12][13][14][15][16][17][18][19][20] Years with mean age as 33.92±17.40 years (Table 1). Male to female ratio is 1.12 with 74 males and 66 females ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the patients (33/140) were in age group of [11][12][13][14][15][16][17][18][19][20] Years with mean age as 33.92±17.40 years (Table 1). Male to female ratio is 1.12 with 74 males and 66 females ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The plain x-ray abdomen was found to be indispensable in imaging of abdominal gas shadows and similar results have been quoted in the literature. [9][10][11] The plain x-ray abdomen could also detect urolithiasis in 4 out of 6 patients. Thus, x-ray abdomen was useful in diagnosis of surgical causes of acute abdomen 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Risks of abdominal pain of moderate to severe, and the obvious clinical symptoms may lead to intestinal obstruction, ureter stones, ischemia, or diseases of the gallbladder (Kellow et al 2008). In a retrospective study it was found that 40% of photo plain radiographs of the abdomen was considered normal had to be followed up with additional advanced checks which discovered the abnormal condition of 72% so the current role of photo plain radiographs of the abdomen benefitted that which was taken over by CT scan and ultrasound.…”
Section: Descriptive Decision-making Modelmentioning
confidence: 99%
“…The decision of the author was primarily intuitive based on recognized pattern of same signs and symptoms that were experienced by other patients with similar cases who eventually (Kellow et al 2008).…”
Section: Introductionmentioning
confidence: 99%